Pelatihan dengan Teknik Inter-Professional Collaboration untuk Meningkatkan Pengetahuan Petugas Puskesmas tentang Gizi Buruk - Kusparlina, Eny Pemilu; Wasito, Eddy (FORUM ILMIAH KESEHATAN, 2022)
Very complex health problems require treatment involving all health professionals. The nutritional status of children is one of the important things to prepare a quality generation. Health education in the form of training is expected to change the competence of collaboration across healthcare professionals. The type of research used is descriptive using a mix method (qualitative and quantitative). This study aims to determine the effect of training on knowledge about collaboration across health professions in handling cases of malnutrition. This research was conducted at the Banjarejo Health Center, Madiun City. The population in this study were all health workers who served at the Banjarejo Health Center. Respondents were 24 people who were obtained by stratified random sampling technique and that was also used as informants. Data was collected in two ways, namely primary data through filling out questionnaires, in-depth interviews with informants and observation. Secondary data in the form of profiles of Health Center, number of health workers and other data needed. The data that has been collected is then tested for normality of the data and presented in the form of a frequency distribution table. Furthermore, because the data on knowledge of malnutrition were not normally distributed, the Wilcoxon test was carried out and knowledge about cross-professional collaboration was normally distributed, a paired t test was performed. For qualitative data, it was analyzed using content analysis and a matrix of informants' statements was compared with the processed quantitative data. Keywords: training; knowledge; poor nutrition; inter-professional collaborationABSTRAK Permasalahan status gizi yang sangat kompleks memerlukan penanganan yang melibatkan ahli gizi kesehatan. Status gizi anak menjadi salah satu hal penting untuk mempersiapkan generasi berkualitas. Pendidikan kesehatan dalam bentuk pelatihan diharapkan mampu mengubah kompetensi kolaborasi lintas profesi petugas kesehatan. Penelitian ini bertujuan untuk mengetahui pengaruh pelatihan terhadap pengetahuan tentang kolaborasi lintas profesi kesehatan pada penanganan kasus gizi buruk. Penelitian ini menerapkan mix method (kualitatif dan kuantitatif). Subyek penelitian adalah 24 petugas kesehatan di Puskesmas Banjarejo, Madiun, yang dipilih dengan teknik stratified random sampling, sekaligus dilibatkan sebagai Informan. Pengumpulan data dilakukan melalui pengisian kuesioner, wawancara mendalam dengan informan dan observasi. Data yang telah dikumpulkan kemudian diuji normalitas data dan disajikan dalam bentuk tabel frekuensi. Selanjutnya dilakukan uji Wilcoxon dan paired sample t-test. Untuk studi kualitatif dilakukan analisis konten dan disusun matriks pernyataan informan untuk perbandingan dengan data kuantitatif.Kata kunci: pelatihan; pengetahuan; gizi buruk; inter-professional collaboration